Massive pleural empyema in infancy - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Pleural empyema is an emergency clinical condition characterised by presence of purulent organisms within the pleural fluid. It is associated with significant morbidity and consumption of scarce resources. It is a rare clinical condition but constitute a serious thoracic emergency despite advances in management. Imaging plays an important role in the diagnosis and management of pleural empyema. We present an 11 month old infant with a month history of fever, cough, shortness of breath and weight loss. Clinical diagnosis of bronchopneumonia with pleural effusion was made. Chest radiograph revealed right opaque hemithorax with central mediastinum. Computed tomography (CT) of the chest showed extensive right pleural effusion with compression of viable lung tissue. Ultrasound guided thoracocentesis drained about one litre of pus. Intravenous antibiotics were also administered. Repeat chest radiograph a week after the drainage showed marked reduction in the size of the previously noted opaque right hemithorax with remarkable improvement of the clinical condition.